Use of Agricultural Wastes for the Immobilization of Metals in Polluted Soils in Lagos State, Nigeria - Aderonke Oluwabukola Oyeyiola; Waheed Adeosun; Idera A. Fabunmi (Journal of Health and Pollution, 2017)
Background. An increase in human and industrial activities has led to an increase in the pollution of soils by metals. If these metals become bioavailable, there is potential for human exposure, leading to possible health effects. Remediation of soils is important to ensure that soil is suitable for agricultural purposes. Objectives. To explore the use of sawdust and cow dung to remediate contaminated soil by reducing the bioavailability of metals. Methods. Soil samples were collected from Oke Afa dumpsite and Owode Onirin metallic store and total metal concentrations were determined by digesting with aqua regia and analyzed using flame atomic absorption spectrophotometry. The effect of varied dosages (1–5%) of cow dung and sawdust on the immobilization of the selected metals was investigated, and results were compared with disodium hydrogen phosphate (DSHP) amendments. A single reagent leaching test was carried out with 0.1 M calcium chloride to determine the bioavailability of metals before and after amendment. Results. Before amendment, the amount of bioavailable metal in the soil sample from Oke Afa dumpsite was 57.5 mg/kg, 194 mg/kg and 17.5 mg/kg for copper (Cu), lead (Pb) and zinc (Zn), respectively, while in the second soil sample, from Owode Onirin metallic store, the amount of bioavailable Cu, Pb and Zn was observed to be 19.9 mg/kg, 36.4 mg/kg and 11.1 mg/kg, respectively. Up to 73.4% of mobile Zn was immobilized using DSHP, while cow dung and saw dust were effective in the immobilization of Cu and Pb, but not Zn. Conclusions. Cow dung and sawdust reduced the bioavailability of copper and lead, while Zn can be effectively immobilized with the use of DSHP. It was generally observed that the bioavailability of heavy metals decreased with increasing dosage of the amendments. Competing Interests. The authors declare no competing financial interests.